Republic of Moldova : 2007 Article IV Consultation and Third Review Under the Three; Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Moldova. (IMF Staff Country Reports; Country Report ;, 2008)
Moldova showed improved growth prospects and decline in poverty despite a series of consecutive shocks under the economic program. Executive Directors commended the balanced macroeconomic policies and urged to maintain macroeconomic stability. They also appreciated the strong monetary policy by National Bank of Moldova (NBM), disciplined fiscal policies, financial sector stability and consolidation of education and health care networks, and stressed the need to strengthen tax administration while maintaining the deficit target. The need for modernization of energy sector and effective implementation of Anti Money Laundering and Combating the Financing of Terrorism (AML/CLT) law were also found to be essential.